[Laiškas] / Augustinovičius (Augustinowicz) Martynas - Adomui Zavadskiui. - (:unkn) unknown (My University, 1854)
1 raštas dėl klaidingos sąskaitos už atsiųstas knygas.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Volkolata (vietovė); Zawadzki, Adam, 1814-1875; Augustinovičius (Augustinowicz), Martynas